DESIGN TRENDS IN CHILDREN'S BOOK ILLUSTRATION - AN EXAMPLE OF LATGALIAN ABC DESIGN - Širiņa, Ieva; Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Children's book illustrations have always been an area that allows artists to make the most of their creative potential. Modern design trends for children's books are changing both in the world and in Latvia. The most relevant of these are minimalism and color purity, simplicity and quality. Research also highlights the choice of illustration and font style in favor of retro style and handwriting. Picture books on the topics of kindness and love are popular in terms of content. Activity books are useful for interactive communication. The aim of the article is to develop the concept of graphic design of the ABC of Latgalian language by studying design trends in children's book illustration and the supply and demand of children's Latgalian literature in Latvia. Research methods: theoretical - research and analysis of literature and Internet resources, empirical - questionnaire, analysis of analogues.